Pendidikan Keluarga Sebagai Ujung Tombak Perilaku dan Moral Anak: Tinjauan Sosiologi - Dwi Narsih (Jurnal Ilmiah Wahana Pendidikan, 2021)
Children's educational activities at home have started to decrease. This is due to shifting times and cultures. Parents are busy, both father and mother do not take the time to educate their children at home. Even though education at home is the main and very strategic education. Both mother and father have a big share in educating children. This research uses descriptive qualitative methods. Retrieval of data by means of interviews, photos and observations. The research subjects were students and parents. The sample consisted of 7 people, consisting of 4 elementary and junior high school students and 3 parents. The study was conducted from early January to March 2020. The results showed that family education was still ignored. This is due to several factors, such as changes in social, economic and cultural roles. Sociological changes appear when the father's role is replaced by the mother, and the mother's role is replaced by the father